Experimental application of EPS concrete in the new prototype design of the concrete barrier. (15th October 2016) - Mohammed, Hasan Jasim; Zain, M.F.M.
Highlights: A new concrete barrier (NCB) is fabricated with a new shape. EPS concrete is applicable in the concrete barrier. The new model absorbs more impact energy using EPS beads. EPS concrete energy dissipation is higher than that of normal concrete. NCB undergoes failure only at the part facing the strike load. Abstract: A new concrete barrier (NCB) design that separates the opposing lanes in roads was presented and tested experimentally. The proposed design comprises three parts. The expanded polystyrene (EPS) beads were used to cast the outer parts with 15%, 30%, and 45% replacement from coarse aggregate by volume with silica fume substituted with 10% of cement. Four pressures were applied to the concrete barrier models (2.3, 3.2, 4.5, and 5.8 MPa), which are respectively equivalent to four operational speeds of the vehicles (50, 70, 100, and 130 km/h). Results showed that the failure occurred only in the outer part facing the strike force, and the other parts did not fail. The use of EPS beads with percentages of 15% and 30% was to absorb the impact loads in a good way, and these percentages are better than 45%. The results demonstrated little lateral deflection. Moreover, the EPS beads led little strains and facilitated to absorb the impact force. The new prototype of concrete barrier can be functional in roads with good energy dissipation, and it has conformed with the requirements of the crash concrete barrier test.